Vertical tectonic movements and sedimentary filling of basins during syn-rift and post-rift stages of lithosphere development - V. V. Gonchar (Геофизический журнал, 2017)
One-dimensional numerical modeling of isostatic response of lithosphere to thermal uplift of its bottom  (active rifting) and interconnected formally independent thinning of the crust has been fulfilled. Evolution curves of vertical movements and interfaces displacements velocities have been examined. Depending on the introduced index of thinning of the crust velocity n=0,1¸3 spectrum of surface expression has been segregated: from the arc rift via annectent forms (n=0,8¸1,5) to deep water depressions. In relation to a set of problems of paleo-tectonic reconstructions of sedimentary basins modeling of vertical movements accompanied by sedimentation was conducted. Situations have been examined when syn-rift sedimentation and dipping are much less than post-rift ones. Possibilities of establishment of conditions and evolution of continental and marine sedimentation within the limits of different regimes of riftogenesis have been investigated. In order to overcome limitations specific to methods of modern back-stripping an expanded variant of direct modeling has been tested based on the principle of «free sedimentation», taking into account facial vertical heterogeneity of the section and stratigraphic  unconformities. In the model which explains formation of the Permian-Triassic sedimentary column of the Ebro depression (Iberia) paleo-geographic features of sedimentation are replicated: it was the continental one in the Permian and early Triassic with transition to marine in the end of Middle Triassic, uncertainty of stratigraphic unconformities of the Late Permian is also revealed. Accordingly, the complicated character of active riftogenesis consisting of two stages is predicted; for the second (Late Permian) variation of regime as three phases with different indices of thinning the crust is provided.